Water repellent member, and method of producing the same
A water-repellent aluminum member with a porous anodic oxide film and fluorine- or silicon-containing compound layer maintains superior water repellency by combining anodization, etching, and plasma treatment, addressing the durability issue of existing technologies.
Patent Information
- Application Number
- JP2023118807
- Authority / Receiving Office
- JP · JP
- Patent Type
- Applications
- Current Assignee / Owner
- Filing Date
- 2023-07-21
- Publication Date
- 2025-01-31
AI Technical Summary
Existing water-repellent aluminum members lose their water-repellent performance over time, necessitating a solution that maintains high water repellency for a prolonged period.
A water-repellent member with a porous anodic oxide film on an aluminum substrate, featuring a tapered wall structure with a crown-shaped profile and a fluorine- or silicon-containing compound layer, formed through anodization, etching, and plasma treatment to enhance durability.
The solution achieves high water repellency that is maintained over a long period, effectively preventing snow, frost, and ice adhesion.
Smart Images

Figure 2025015913000001_ABST
Abstract
Description
[Technical field]
[0001] The present invention relates to a water-repellent member and a manufacturing method thereof, and more particularly to an aluminum member having an aluminum base material made of aluminum or an aluminum alloy and an anodized coating film formed on the surface of the aluminum base material, and a water-repellent material layer containing a water-repellent material and covering the surface of the anodized coating film of the aluminum member, and a manufacturing method thereof. [Background technology]
[0002] By forming a nano-relief structure on an aluminum substrate and providing a water-repellent material layer containing a water-repellent material on the surface after the nano-relief structure is formed, an aluminum component is provided with improved water-repellent performance and performance in preventing snow, frost, or ice (hereinafter, these will be collectively referred to simply as "water-repellent performance").Among these, a method for forming a nano-relief structure to improve water-repellent performance is to form a porous anodized film on the aluminum substrate by anodizing treatment.
[0003] For example, Patent Document 1 describes a method for producing a water-repellent member having a liquid-repellent surface by forming a porous coating on an aluminum substrate by anodization using sulfuric acid, widening the pores by acid etching using phosphoric acid, activating the substrate by oxygen plasma treatment, and further coating the resulting porous surface with a hydrocarbon oil containing zinc dialkyldithiophosphate (ZnDTP).
[0004] Furthermore, Patent Document 2 describes how an aluminum substrate is anodized to form a porous coating, then activated by imparting functional groups through surface plasma treatment, and then treated with a silane coupling agent to provide a water-repellent layer, thereby providing a water-repellent member with a water-repellent surface.
[0005] Furthermore, Patent Document 3 describes a method of treating an aluminum substrate with primary and secondary anodization, followed by pore widening using a phosphoric acid solution, to obtain a water-repellent material having a superhydrophobic surface with a pillar-on-pore structure in which sharp pillars are formed individually or in bundles at the top of the pores.
[0006] Furthermore, Patent Document 4 describes that by repeatedly performing anodizing treatment (anodizing treatment) and etching treatment on an aluminum base material, a regular uneven structure in which numerous pin-shaped protrusions stand side by side is formed, and further, by forming an anodized layer in which the contact area ratio of the pin-shaped protrusions of the uneven structure is small, the water repellency of a water-repellent coating formed on the surface is improved. [Prior art documents] [Patent documents]
[0007] [Patent Document 1] JP 2021-116451 A [Patent Document 2] Special Publication No. 2014-509959 [Patent Document 3] Special Publication No. 2022-524167 [Patent Document 4] JP 2017-115219 A Summary of the Invention [Problem to be solved by the invention]
[0008] As mentioned above, it has been considered to form a nano-order uneven structure by anodizing an aluminum substrate, and to provide a water-repellent material layer containing a water-repellent material on the surface. This makes it possible to obtain a water-repellent member that has water-repellent properties and the ability to prevent snow, frost, or ice from accumulating. However, all of these methods focus on increasing water repellency in the initial stages of production.
[0009] An object of the present invention is to provide a water-repellent member that can maintain water repellency not only at the initial stage of production but also over a long period of time. Another object of the present invention is to provide a method for producing a water-repellent member that can obtain such a water-repellent member. [Means for solving the problem]
[0010] The inventors conducted further research into conventionally known water-repellent materials, namely, water-repellent materials in which an aluminum base material is anodized to form a nano-order uneven structure, and a water-repellent material layer containing a water-repellent material is provided on the surface of the structure, and as a result, they came to the new knowledge that if one tries to improve the water-repellent performance, it becomes difficult to maintain that performance over the long term.
[0011] Therefore, the inventors have conducted extensive research into this problem and have discovered that by repeatedly performing anodizing and etching treatments on an aluminum substrate, and combining the formation of a porous anodizing film by anodizing treatment with pore widening by etching treatment to form a porous layer having holes and walls of a specified shape, it is possible to achieve high water-repellent performance while maintaining that water-repellency for a long period of time, thereby completing the present invention.
[0012] That is, the gist of the present invention is as follows. (1) A water-repellent member comprising an aluminum member having an aluminum base material made of aluminum or an aluminum alloy and an anodized coating formed on the surface of the aluminum base material, and a water-repellent material layer containing a water-repellent material and covering a surface of the anodized coating of the aluminum member, wherein the water-repellent material layer contains at least one compound selected from the group consisting of fluorine-containing compounds and silicon-containing compounds, the anodized coating has a porous layer having bottomed holes opening to the surface and wall portions standing around the holes, the wall portions have a tapered shape that narrows in width from the base side to the tip side, the wall portions have a crown-shaped structure in which a middle portion of the wall portion sandwiched between two adjacent holes is relatively low in height and a middle portion of the wall portion surrounded by three or more adjacent holes is relatively high in height, and the hole portions have a ratio (H / W) of a depth (H) of the hole portions to a spacing (W) between the hole portions is 1 or more and 4 or less. (2) The water-repellent member described in (1), wherein the wall portion has a tapered shape that narrows from the base side to the tip side, and has a protrusion that protrudes and expands in the width direction at the most distal end of the central part of the wall portion. (3) The water-repellent member according to (1) or (2), wherein the anodized coating has a standard deviation of the angle (θp) of the holes of 3 or more. (4) The water-repellent member according to any one of (1) to (3), wherein the anodized coating has a base width (Ww) of the wall portion of 100 nm or more. (5) The water-repellent member according to any one of (1) to (4), wherein the anodized film has a thickness of 1 μm or less. (6) The water-repellent member according to any one of (1) to (5), wherein the anodized coating has a domain structure in which a recess is formed by a group of a plurality of the holes sandwiching a wall portion that is shorter in height than the surrounding wall portions. (7) The water-repellent member according to any one of (1) to (6), which is a condensation prevention member.
[0013] (8) A method for producing a water-repellent member comprising an aluminum member having an aluminum base material made of aluminum or an aluminum alloy and an anodized film formed on the surface of the aluminum base material, and a water-repellent material layer comprising a water-repellent material and covering the surface of the anodized film of the aluminum member, the method comprising the steps of: repeatedly performing an anodizing treatment on the aluminum base material using an electrolyte containing oxalic acid; and etching treatment on the aluminum base material using a treatment liquid containing phosphoric acid; forming a porous anodized film by the anodizing treatment; and widening the pores by the etching treatment, thereby forming a porous layer having bottomed holes opening on the surface and walls standing around the holes, the walls having a tapered shape narrowing from the base side to the tip side, and a center of the wall between two adjacent holes. a coating treatment step of irradiating the anodized film formed by the coating formation step with plasma treatment to impart functional groups to the anodized film, thereby activating the anodized film; and a water-repellent step of providing the water-repellent material layer on the surface of the anodized film by performing a water-repellent treatment on the anodized film activated by the coating treatment step using an aqueous solution containing a water-repellent material made of at least one compound selected from the group consisting of fluorine-containing compounds and silicon-containing compounds, wherein the holes in the anodized film have a ratio (H / W) of the depth (H) of the holes to the spacing (W) of the holes in the anodized film is 1 or more and 4 or less. (9) The method for producing a water-repellent member according to (8), wherein the plasma treatment is an oxygen plasma treatment in which hydroxyl groups are imparted to the anodized film by exposure to oxygen plasma. (10) The method for producing a water-repellent member according to (8) or (9), wherein in the film forming step, the surface roughness (Ra) of the aluminum base material on which the anodizing treatment and the etching treatment are performed is 0.1 μm or more. Effect of the Invention
[0014] The water-repellent member of the present invention exhibits high water repellency and can maintain the water-repellent performance for a long period of time. [Brief description of the drawings]
[0015] [Figure 1] FIG. 1 is a cross-sectional SEM image illustrating how the wall portion of the porous layer of the anodic oxide coating has a tapered shape that narrows from the base side to the tip side. [Diagram 2] FIG. 2 is an SEM image of the surface of the porous layer observed from an oblique direction to show how the walls of the porous layer of the anodic oxide coating have a crown-shaped structure. [Diagram 3] FIG. 3 is an enlarged view of the area enclosed by the white solid line in FIG. 2, and shows that the walls of the porous layer have a crown-shaped structure. [Figure 4] FIG. 4 is an enlarged view of the area surrounded by the white dashed line in FIG. 2, and is intended to show that the central portion of the wall portion surrounded by three or more adjacent holes has a protrusion at its most distal end that protrudes and extends in the width direction of the wall portion. [Diagram 5] FIG. 5 is an example of an SEM image (Example 1) showing the surface of the porous layer of the anodized film used to determine the spacing (W) between the pores. [Figure 6] FIG. 6 is an example (Example 1) of a cross-sectional SEM image of the porous layer of the anodized film used to determine the depth (H) of the pores. [Figure 7] FIG. 7 is an example (Example 1) of a cross-sectional SEM image of the porous layer of the anodized film used to determine the angle (θp) of the hole. [Figure 8] FIG. 8 is an explanatory diagram that shows a schematic diagram of a procedure for determining the angle (θp) of the hole. [Figure 9] FIG. 9 is an example (Example 1) of a cross-sectional SEM image of the porous layer of the anodized film used to determine the base width (Ww) of the wall portion. [Figure 10]FIG. 10 is an example (Example 1) of a cross-sectional SEM image of a porous layer of an anodized film used to determine the film thickness of the anodized film. [Figure 11] FIG. 11 is an example (Example 1) of a planar SEM image (planar) showing the domain structure that can be confirmed in the porous layer of the anodic oxide coating. [Figure 12] FIG. 12 is a cross-sectional SEM image used to determine the pore depth (H) of the porous layer in the anodized film of the water-repellent member of Example 2. [Figure 13] FIG. 13 shows tilted SEM images of the surface of the porous layer in the anodized coating of the water-repellent member, where (a) is for Example 2, (b) is for Example 3, (c) is for Comparative Example 1, and (d) is for Comparative Example 2. [Figure 14] FIG. 14 shows tilted SEM images of the surface of the porous layer in the anodized coating of a water-repellent member, where (a) is for Comparative Example 3, (b) is for Comparative Example 4, (c) is for Comparative Example 5, and (d) is for Comparative Example 6. [Figure 15] FIG. 15 is an SEM image (tilted) showing the surface of the porous layer in the anodized film of the water-repellent member, and shows the case of Comparative Example 7. [Figure 16] FIG. 16 shows planar (surface) SEM images used to determine the spacing (W) of holes in the porous layer in the anodized coating of a water-repellent member, where (a) is for Example 2, (b) is for Example 3, (c) is for Comparative Example 1, and (d) is for Comparative Example 2. [Figure 17] FIG. 17 shows planar (surface) SEM images used to determine the spacing (W) of holes in the porous layer in the anodized coating of a water-repellent member, where (a) is for Comparative Example 6, (b) is for Comparative Example 7, and (c) is for Comparative Example 8. [Figure 18] FIG. 18 is a cross-sectional SEM image used to determine the angle (θp) of the pores in the porous layer in the anodized film of the water-repellent member in accordance with Example 2. [Figure 19]FIG. 19 shows cross-sectional SEM images used to determine the base width (Ww) of the wall of the porous layer in the anodized coating of a water-repellent member, where (a) is for Example 2, (b) is for Example 3, (c) is for Comparative Example 1, and (d) is for Comparative Example 5. [Figure 20] FIG. 20 shows cross-sectional SEM images used to determine the base width (Ww) of the wall of the porous layer in the anodized coating of the water-repellent member, where (a) is for Comparative Example 6, (b) is for Comparative Example 7, and (c) is for Comparative Example 8. [Figure 21] FIG. 21 shows cross-sectional SEM images used to determine the thickness of the anodized film on the water-repellent member, where (a) is for Example 2, (b) is for Example 3, (c) is for Comparative Example 1, and (d) is for Comparative Example 2. [Figure 22] FIG. 22 shows cross-sectional SEM images used to determine the thickness of the anodized film on the water-repellent member, where (a) is for Comparative Example 3, (b) is for Comparative Example 4, (c) is for Comparative Example 5, and (d) is for Comparative Example 6. [Figure 23] FIG. 23 shows cross-sectional SEM images used to determine the thickness of the anodized film on the water-repellent member, where (a) is the case of Comparative Example 7 and (b) is the case of Comparative Example 8. [Figure 24] FIG. 24 shows SEM images (plan view) of the surface of the porous layer of the anodized film of the water-repellent member, where (a) is for Example 2, (b) is for Example 3, (c) is for Comparative Example 1, and (d) is for Comparative Example 2. [Diagram 25] FIG. 25 shows SEM images (plan view) of the surface of the porous layer of the anodized coating of the water-repellent member, where (a) is for Comparative Example 3, (b) is for Comparative Example 4, (c) is for Comparative Example 5, and (d) is for Comparative Example 6. [Figure 26] FIG. 26 is an SEM image (plan view) of the surface of the porous layer of the anodized film of the water-repellent member, showing the case of Comparative Example 7. [Figure 27] FIG. 27 is a cross-sectional SEM image used to determine the pore depth (H) of the porous layer in the anodized film of the water-repellent member of Example 3. [Figure 28] FIG. 28 is a cross-sectional SEM image used to determine the angle (θp) of the pores in the porous layer in the anodized film of the water-repellent member in accordance with Example 3. [Figure 29] FIG. 29 is a cross-sectional SEM image used to determine the pore depth (H) of the porous layer in the anodized film of the water-repellent member in Comparative Example 1. [Diagram 30] FIG. 30 is a cross-sectional SEM image used to determine the angle (θp) of the pores in the porous layer in the anodized film of the water-repellent member in accordance with Comparative Example 1. [Diagram 31] FIG. 31 is a cross-sectional SEM image used to determine the pore depth (H) of the porous layer in the anodized film of the water-repellent member in Comparative Example 5. [Diagram 32] FIG. 32 is a cross-sectional SEM image used to determine the pore depth (H) of the porous layer in the anodized film of the water-repellent member in Comparative Example 6. [Diagram 33] FIG. 33 is a cross-sectional SEM image used to determine the pore depth (H) of the porous layer in the anodized film of the water-repellent member in Comparative Example 7. [Diagram 34] FIG. 34 is a cross-sectional SEM image used to determine the pore depth (H) of the porous layer in the anodized film of the water-repellent member in Comparative Example 8. [Diagram 35] FIG. 35 is a cross-sectional SEM image used to determine the angle (θp) of the pores in the porous layer in the anodized film of the water-repellent member in Comparative Example 8. [Diagram 36] FIG. 36 is a set of photographs showing the results of a condensation evaluation of the water-repellent member of Example 1 and the hydrophilic member of Comparative Example 8. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0016] The water-repellent member of the present invention will be described in detail together with the manufacturing method thereof. The components of the present invention described below can be combined in part or in whole as appropriate.
[0017] [1. Water-repellent materials] The water-repellent member of the present invention comprises an aluminum member having an aluminum base material made of aluminum or an aluminum alloy and an anodized coating formed on the surface of the aluminum base material, and a water-repellent material layer comprising a water-repellent material and covering the surface of the anodized coating of the aluminum member, the water-repellent material layer containing at least one compound selected from the group consisting of fluorine-containing compounds and silicon-containing compounds, the anodized coating has a porous layer having bottomed holes opening to the surface and wall portions standing around the holes, the wall portions having a tapered shape that narrows in width from the base side to the tip side, a crown-shaped structure in which the height of an intermediate portion of the wall portion sandwiched between two adjacent holes is relatively low and the height of a central portion of the wall portion surrounded by three or more adjacent holes is relatively high, and the holes have a ratio (H / W) of the depth (H) of the hole to the spacing (W) between the hole portions is 1 or more and 4 or less.
[0018] [1-1. Aluminum components] <Aluminum substrate> The water-repellent member of the present invention comprises an aluminum member and a water-repellent material layer, and the aluminum member has an aluminum base material made of aluminum or an aluminum alloy and an anodized coating formed on the surface of the aluminum base material. The aluminum base material used in this aluminum member is made of aluminum or an aluminum alloy. There are various aluminum base materials, ranging from pure aluminum with a purity of 100% to aluminum alloys with different types and amounts of alloying elements. The material is not limited, and can be determined based on the application of the water-repellent member formed using it and various physical properties required for the application, such as strength, corrosion resistance, and processability. In addition, processed materials obtained by appropriately processing into a desired shape, and combined materials obtained by appropriately combining these processed materials, etc., can also be used.
[0019] Among these, when considering cases in which the material is used to form a component forming a refrigerator compartment or a case for a notebook computer, for example, a wrought material that is excellent in thermal conductivity and easy to process is desirable, and among these, it is preferable to use 1000 series alloys, 3000 series alloys, 5000 series alloys, and 6000 series alloys. In addition, although there are no particular limitations since it depends on the application of the water-repellent member, the thickness of the aluminum substrate that can be used is generally about 0.3 mm to 10 mm.
[0020] <Anodized film> The aluminum substrate has an anodized coating on its surface. The anodized coating has a porous layer including bottomed holes (generally also called holes or pores) that open to the surface and walls that stand around the holes. Of these, the wall portion has a tapered shape in which the width narrows from the base side of the wall portion toward the tip side, as shown by the dashed line in the cross-sectional image taken by a scanning electron microscopy (SEM) in Figure 1. In addition, as can be seen from the SEM image of the surface observed from an oblique direction in Figure 2, this wall portion has a crown-like structure in which the height of the middle part sandwiched between two adjacent holes is relatively low, and the height of the center part of the wall portion surrounded by three or more adjacent holes is relatively high. These aspects are explained in detail in Figure 3.
[0021] That is, Fig. 3 is an enlarged view of the area surrounded by the white solid line in Fig. 2. For example, when focusing on two adjacent holes h1 and h2, the wall W sandwiched between them has a relatively low height at its middle (the middle is concave). When focusing on three adjacent holes h1, h2, and h3, the height of the center C of the wall W surrounded by these holes is relatively high. In other words, the height of the center C where the wall W intersects surrounded by three or more adjacent holes is relatively high, and at the tip of the wall W, the ridge line connecting the adjacent center parts C across the middle part is curved and convex toward the inside of the wall W, so that the wall W in the porous layer can be said to have a crown-shaped structure.
[0022] As described above, the wall portion has a tapered shape in which the width narrows from the base side to the tip side, and some of the walls have a protrusion that protrudes and spreads in the width direction of the wall portion at the most distal end of the central portion C described above. That is, FIG. 4 is an enlarged view of the area surrounded by the white dashed line in FIG. 2, and it can be seen that the most distal end of the central portion C of the wall portion surrounded by three or more adjacent holes has a protrusion C1 that protrudes and spreads in the width direction of the wall portion like a whisker (area surrounded by a dashed line). As will be described in the examples below, it is preferable that more of the most distal end of the central portion C of the wall portion has the protrusion C1, and the presence of this protrusion C1 makes it easier to improve the durability of the water repellency.
[0023] On the other hand, the ratio (H / W) of the depth (H) of the holes to the interval (W) of the holes is 1 or more and 4 or less. In the present invention, the ratio (H / W) of the depth (H) of the holes to the interval (W) of the anodic oxide coating is in a relatively low numerical range, so that excellent water repellency can be exhibited and the performance can be maintained for a long period of time. This ratio (H / W) is preferably 1.5 or more, more preferably 2 or more, and even more preferably 2.5 or more. On the other hand, this ratio (H / W) is preferably 3.8 or less, more preferably 3.5 or less, and even more preferably 3.2 or less. Of these, the interval (W) of the holes is preferably 100 nm or more, more preferably 130 nm or more, and even more preferably 160 nm or more, and preferably 250 nm or less, more preferably 200 nm or less, and even more preferably 180 nm or less. The depth (H) of the pores is preferably 200 nm or more, more preferably 300 nm or more, and even more preferably 400 nm or more, and is preferably 1000 nm or less, more preferably 800 nm or less, and even more preferably 600 nm or less.
[0024] Here, the distance (W) between the holes was determined in the following manner in the embodiment of the present invention. That is, FIG. 5 illustrates the case of Example 1. First, in a planar SEM photograph of the porous layer of the anodized film taken at a predetermined magnification (50,000 times in Example 1, the values in parentheses below are exemplified for Example 1), three transverse lines L1 to L3 were arbitrarily drawn across the photograph. This photograph was printed, and the length of the scale (200 nm) on the photograph and the lengths of the transverse lines L1 to L3 were actually measured (in mm), and the lengths (nm) of the transverse lines L1 to L3 were calculated from these values. The length of the transverse lines L1 to L3 refers to the length of the portion crossing the image out of the total length of the drawn transverse lines L1 to L3.
[0025] Next, the number of holes passing through or in contact with each of the transverse lines L1 to L3 was counted (14 for L1, 15 for L2, and 15 for L3). Then, the average number of holes passing through or in contact with each of the three cross lines L1 to L3 was divided by the length (nm) of the cross lines L1 to L3 to determine the hole spacing. Finally, the average value of the spacing between the holes in contact with the three cross lines L1 to L3 was calculated to obtain the hole spacing Wp in the embodiment described later.
[0026] In addition, in determining the depth (H) of the hole, the following procedure was followed in the embodiment of the present invention. That is, FIG. 6 is an example of the case of Example 1, and is an image of a cross-sectional SEM photograph of the porous layer of the anodized film taken at a predetermined magnification (50,000 times in Example 1, the numerical values in parentheses below are examples of the case of Example 1). Here, for one hole sandwiched between adjacent walls, a straight line L21 was drawn connecting the tip portions (tops) of the adjacent walls. In addition, a straight line L31 was drawn connecting the midpoint of the straight line L21 and the tip portion (bottom) of the hole. This photograph was printed, and the length of the scale (200 nm) on the photograph and the length of the straight line L31 were actually measured (in mm), and the depth of the hole corresponding to the length of the straight line L31 was calculated based on the length of the scale.
[0027] This procedure was carried out at 10 locations where holes could be confirmed, and straight lines L21-L30 were drawn connecting the tip portions (tops) of adjacent walls, and straight lines L31-L40 were drawn connecting the midpoints of these straight lines to the tip portions (bottoms) of the holes to calculate the depths of the 10 holes in the same manner. The average value of the depths of the 10 holes was then calculated to obtain the depth Hp of the hole in the embodiment described below. In determining the depth (H) of the hole in this manner, in addition to the hole in which the internal space is exposed in the cross-sectional SEM photograph, the hole in which the wall portion in front of the hole can be seen through is also measured.
[0028] In addition, the pore diameter (opening pore diameter) D of the pores opening on the surface of the anodized coating is preferably 80 nm or more and 300 nm or less. By having the pore diameter D of the pores within this range, excellent water repellency can be more reliably exhibited and maintained for a long period of time. The pore diameter D of the pores is preferably 100 nm or more, more preferably 140 nm or more, and is preferably 200 nm or less, more preferably 170 nm or less.
[0029] Here, in the embodiment of the present invention, the pore diameter D of the hole was calculated as follows. That is, referring to the example of FIG. 5, a 50,000-fold planar SEM photograph was used to measure the interval between the holes to measure the pore diameter D of the opening (the magnification of the SEM photograph is not limited to this). This photograph was printed, and the length of the scale (200 nm in FIG. 5) on the photograph and the length of each of the three straight lines (transverse lines) L1 to L3 that pass through or contact the three straight lines (transverse lines) L1 to L3, and the maximum diameter (maximum pore diameter) of the opening at the position where the diameter is the largest was actually measured (here, in mm units). The maximum pore diameter of the opening of the hole was calculated based on the length of the scale. The maximum pore diameter (here, in nm units) of all the holes that pass through or contact each of the transverse lines L1 to L3 was calculated, that is, the maximum pore diameter (nm) of all the holes was calculated by moving L1 to L3 shown in FIG. 5 up and down, and the average value of all the maximum pore diameters was taken as the pore diameter D of the opening.
[0030] Also, it is preferable that the holes are arranged in the anodized film with an inclination. That is, as the inclined holes, the angle θp of the holes with respect to the aluminum base material is preferably 85° or more and 95° or less, and preferably the angle θp is 88° or more. Also, it is preferable that the angle θp is 92° or less. Furthermore, it is preferable that the inclination of the holes is irregular (has variation) in the anodized film. Specifically, the variation (standard deviation) of the hole angles is preferably 3 or more and 12 or less, preferably 4 or more, and more preferably 5 or more. On the other hand, the variation (standard deviation) of the hole angles is preferably 11 or less, and more preferably 10 or less. When the standard deviation of the hole angles θp is equal to or more than the lower limit of the above numerical range, the holes are arranged irregularly, and the surface shape of the anodized film becomes a three-dimensionally complex shape, which makes it easier to exhibit water repellency.
[0031] Here, in the embodiment of the present invention, the angle θp of the hole was obtained as follows. That is, FIG. 7 illustrates the case of Example 1 as in FIG. 6, and is an image of a cross-sectional SEM photograph of the porous layer of the anodized film taken at a predetermined magnification (50,000 times in Example 1). As in the case of obtaining the depth (H) of the hole, for one hole sandwiched between adjacent walls, a straight line L31 was drawn connecting the midpoint of the straight line L21 connecting the tip portions (tops) of the adjacent walls and the tip portion (bottom) of the hole. Here, while using the same image as in FIG. 6, the straight lines L21-L30 connecting the tip portions (tops) of the adjacent walls and the straight lines L31-L40 connecting the midpoint of these straight lines and the tip portion (bottom) of the hole were drawn as in the case of FIG. 6, and the angles of the 10 holes were obtained as follows, but in obtaining the angle θp of the hole, it is not necessary to use the same straight lines L21-L30 and L31-L40 as in obtaining the depth (H) of the hole. Also, different holes may be selected for the ten holes. To repeat, in Fig. 7, the angles of the ten holes are obtained using the same straight lines L21-L30 and L31-L40 as in Fig. 6, but the straight lines L21 and L24, and the straight lines L31 and L34 are shown as representative examples in the figure. Also, these straight lines L21-L30 and L31-L40 are shown as dashed lines in Fig. 7.
[0032] Next, a straight line L61 parallel to the vertical outer edge of the cross-sectional SEM photograph in FIG. 7 was drawn so as to pass through the tip portion (bottom portion) of the hole. In addition, a straight line L71 parallel to the horizontal outer edge of the cross-sectional SEM photograph was drawn so as to pass through the midpoint of the straight line L21 connecting the tip portions (top portions) of the adjacent wall portions across the hole, and perpendicularly intersect with the previous straight line L61. Here, the vertical outer edge of the cross-sectional SEM photograph is approximately parallel to the film thickness growth direction of the anodized film on the aluminum base material, and the horizontal outer edge of the cross-sectional SEM photograph is approximately perpendicular to the film thickness growth direction of the anodized film on the aluminum base material. This created a right-angled triangle where the straight lines L31, L61, and L71 intersect. From the length a of the line segment corresponding to the straight line L61 of this triangle and the length b of the line segment corresponding to the straight line L71, b / a was calculated and entered into the arctan formula to calculate the angle formed by the straight lines L31 and L61. Furthermore, a straight line L81 that is parallel to the outer edge on the horizontal side of the cross-sectional SEM photograph in Fig. 7 and extends from the tip (bottom) of the hole to the right side of the cross-sectional SEM photograph was used as a reference, and the counterclockwise angle from the straight line L81 to the straight line L31 was calculated, and this angle was determined as the angle of the hole. In other words, if the hole is straight with respect to the outer edge on the vertical side of the cross-sectional SEM photograph, the angle is 90°. If the hole is tilted to the left, the angle is larger than 90°, and conversely, if the hole is tilted to the right, the angle is smaller than 90°.
[0033] In this way, the angles of the 10 holes were calculated in the same manner by drawing straight lines L21-L30, L31-L40, L61-70, L71-80, and L81-L90 for the 10 locations where the holes could be confirmed. The average value of the angles of the 10 holes was then calculated to obtain the hole angle θp. In addition, the standard deviation was calculated as the variation in the hole angle θp calculated in this way. The standard deviation was calculated by squaring the differences between each value of the 10 target hole data points and the average value, summing them up, and then dividing the result by the total number of data points (10) and taking the positive square root. The procedure for calculating the hole angle θp in this way is explained in FIG. 8 using straight lines L24, L34, L64, L74, and L84 as examples.
[0034] In addition, the ratio (Hw / Ww) of the wall height (Hw) to the base width (Ww), which is the width at the base, of the wall is preferably 1 or more and 5 or less. As in the case of the holes, in the present invention, by setting the ratio (Hw / Ww) in the wall of the anodized film to a relatively low numerical range, excellent water repellency can be more reliably exhibited and the performance can be more reliably maintained over a long period of time. The ratio (Hw / Ww) is preferably 1.3 or more, more preferably 1.6 or more, and even more preferably 2 or more, and is preferably 4.5 or less, more preferably 4 or less, and even more preferably 3.5 or less.
[0035] Among these, the base width (Ww) of the wall portion is preferably 100 nm or more and 300 nm or less. The base width (Ww) of the wall portion is preferably 140 nm or more, more preferably 170 nm or more, and is preferably 250 nm or less, more preferably 200 nm or less.
[0036] On the other hand, the wall height Hw is preferably 200 nm or more and 1000 nm or less, and more preferably 300 nm or more, more preferably 400 nm or more, and is preferably 800 nm or less, more preferably 700 nm or less.
[0037] Here, in determining the base width Ww of the wall portion, the following procedure was followed in the embodiment of the present invention. That is, FIG. 9 illustrates the case of Example 1, similarly to FIG. 6, and is an image of a cross-sectional SEM photograph of a porous layer of an anodized film taken at a predetermined magnification (here, 50,000 times). Using this cross-sectional SEM photograph, a straight line L41 was drawn connecting the base portions of the adjacent holes, where the approximately semicircular bottoms of the adjacent holes stood up straight across the wall portion, for one wall portion sandwiched between adjacent holes. This photograph was printed, and the length of the scale (here, 200 nm) on the photograph and the length of the straight line L41 were actually measured (here, in mm units). Based on the length of the scale, the base width of the wall portion (here, in nm units) corresponding to the length of the straight line L41 was calculated. The base width of the wall portion at five points was calculated in the same manner by drawing straight lines L41 to L45 at five points where the wall portion could be confirmed. The base width of the wall portion (Ww) was obtained by averaging the base widths of the wall portion at the five points.
[0038] In addition, when calculating the wall height Hw, a straight line L51 was drawn connecting the midpoint of a straight line L41 drawn between the roots of the approximately semicircular bottoms of the adjacent holes, which are raised in a straight line across the wall, and the apex of the wall between the adjacent holes, using FIG. 9 as well. Similarly, the length of the scale (here, 200 nm) on the photograph and the length of the straight line L51 were measured. Based on the length of the scale, the wall height (here, in nm units) corresponding to the length of the straight line L51 was calculated. The wall heights at five points were calculated in the same manner by drawing straight lines L41-45 and L51-L55 at five points where the wall could be confirmed. The wall heights at the five points were averaged to obtain the average wall height (Hw).
[0039] In addition, the anodized film preferably has a thickness of 1 μm or less. If the thickness of the anodized film is 1 μm or less, the collapse of the porous layer can be prevented, and the water repellency can be preferably maintained for a long period of time. The thickness of the anodized film is preferably 800 nm or less, more preferably 700 nm or less, and even more preferably 600 nm or less. On the other hand, from the viewpoint of preferably securing the water repellent material layer described later, the thickness of the anodized film is preferably 300 nm or more, more preferably 400 nm or more, and even more preferably 500 nm or more.
[0040] Here, in the embodiment of the present invention, the thickness of the anodized film was determined as follows. That is, FIG. 10 illustrates the case of the embodiment 1 as in FIG. 6, and is an image of a cross-sectional SEM photograph of the porous layer of the anodized film taken at a predetermined magnification (50,000 times in this case). This image was measured using a backscattered electron image of the cross-sectional SEM. The backscattered electron image shows the difference in brightness between the Al base (Al only) and the anodized film (containing Al and O) due to the difference in element distribution. In other words, the Al base (Al base material) looks whitish, and the anodized film looks blackish. The thickness of the anodized film can be measured by utilizing this shading. In the image, a straight line corresponding to the film thickness was drawn from the boundary between the Al base and the anodized film to the surface of the anodized film, and the length of the scale (200 nm in this case) on the photograph and the length of the straight line were actually measured (in mm here), and the film thickness corresponding to the length of the straight line was measured at three points based on the length of the scale, and the thicknesses of the three points were averaged to obtain the thickness (T) of the anodized film.
[0041] The anodized film may have a domain structure (partial structure) D in which recesses are formed by a group of holes sandwiching walls that are shorter than the surrounding walls, as shown in Fig. 11. The mechanism by which this domain structure is formed, together with the inclined holes described above, is not entirely clear, but it is presumed to be influenced by the surface condition of the aluminum base material on which the anodization treatment is performed, as described later in the method for producing a water-repellent member. Fig. 11 is a planar SEM photograph of the surface of the anodized film according to Example 1, taken at a magnification of 10,000 times.
[0042] [1-2. Water-repellent material layer] <Water-repellent material> The water-repellent member of the present invention comprises the aluminum member described above and a water-repellent material layer. The water-repellent material layer contains a water-repellent material and is formed by covering the surface of the anodized film of the aluminum member with the water-repellent material. Here, the water-repellent material layer contains at least one compound selected from the group consisting of fluorine-containing compounds and silicon-containing compounds as the water-repellent material. Among these, the fluorine-containing compound is an organic compound containing a fluorine atom, and examples thereof include a fluorine-containing coupling agent, a fluorine resin, and a fluorine-based lubricating oil. The silicon-containing compound is an organic compound containing silicon atoms, and examples of the silicon-containing compound include silicon-containing coupling agents, silicone resins, silicone oils, and silicone elastomers.
[0043] Here, examples of the coupling agent include a fluorine-containing coupling agent containing a fluorine atom and a silicon-containing coupling agent containing a silicon atom. As the coupling agent, a silane-containing coupling agent having a structure in which a hydrolyzable group is bonded to a silicon atom is preferable. Among the fluorine-containing coupling agents, a fluorine-containing silane coupling agent is preferable. Among the silicon-containing coupling agents, a silicon-containing silane coupling agent is preferable. The silane-containing coupling agent has, for example, an alkoxy group such as an ethoxy group, a methoxy group, or a butoxy group as a hydrolyzable group, and preferably has an alkoxysilyl group such as an ethoxysilyl group, a methoxysilyl group, or a butoxysilyl group in which the hydrolyzable group is bonded to a silicon atom. By using the silane-containing coupling agent, the alkoxy group of the silane-containing coupling agent is hydrolyzed to generate a silanol group. Then, the silanol group of the silane-containing coupling agent and the hydroxyl group present on the surface of the anodized film of the aluminum member form a hydrogen bond or form a siloxane bond by a dehydration condensation reaction. By using the silane-containing coupling agent in this manner, the fluorine-containing compound and the silicon-containing compound tend to be present stably on the surface of the aluminum member.
[0044] The water-repellent material layer may contain both a fluorine-containing coupling agent and at least one of a fluorine resin and a silicone resin. The water-repellent material layer may contain both a silicon-containing coupling agent and at least one of a fluorine resin and a silicone resin. The water-repellent material layer may contain both a fluorine-containing silane coupling agent and at least one of a fluorine resin and a silicone resin.
[0045] In forming such a water-repellent material layer, the water-repellent material is not particularly limited, but for example, the following fluorine-containing compounds and silicon-containing compounds can be used. That is, examples of the fluorine-containing compound include fluorine-containing silane coupling agents such as perfluorododecyltrichlorosilane (FTCS) and perfluoroalkoxysilane; fluororesins such as polytetrafluoroethylene (PTFE), polychlorotrifluoroethylene (PCTFE) and perfluoroalkoxysilane (PFA); fluorine-based lubricants such as perfluoropolyether (PFPE); etc. Examples of the silicon-containing compound include silicon-containing silane coupling agents such as octyltriethoxysilane and dodecyltriethoxysilane; silicone resins; silicone oils; silicone elastomers; etc.
[0046] [1-3. Water-repellent materials] The water-repellent member of the present invention is a member that suppresses adhesion of water by exhibiting water repellency. In addition to liquid water, the objects to be suppressed from adhesion include solid water or snow, frost, and ice formed by condensation of moisture (water vapor) in the air. In addition, since the water-repellent member of the present invention uses an aluminum base material, it is advantageous in terms of processability. Therefore, the water-repellent member of the present invention has a wide variety of uses and is not particularly limited, but can be used, for example, as a condensation prevention member, a snow-adhesion prevention member, a frost-adhesion prevention member, an ice-adhesion prevention member, and the like. More specifically, it can be used as an aluminum member that forms the walls, ceilings, floors, shelves, and heat exchangers of the refrigerator compartment in a refrigerator, the indoor unit of an air conditioner, and the like, for preventing condensation; the heat exchangers of the indoor units of refrigeration devices used in refrigerated and frozen vehicles and refrigerated and frozen freezers, the heat exchangers of the outdoor units of air conditioners, and the like, for preventing snow and ice; buildings, traffic signs, traffic lights, power lines, steel towers, bridge girders, and the like, which are used outdoors; and the housings of precision instruments such as notebook computers and electronic devices.
[0047] [2. Method of manufacturing water-repellent materials] The method for producing a water-repellent member according to the present invention involves repeatedly performing an anodizing treatment, in which an anodizing treatment is performed using an electrolyte containing oxalic acid, on an aluminum substrate made of aluminum or an aluminum alloy, and an etching treatment, in which an etching treatment is performed using a treatment solution containing phosphoric acid, to form a porous anodized coating by the anodizing treatment, and pore widening by the etching treatment, thereby forming a porous layer having bottomed holes opening on the surface and wall parts standing around the holes, the wall parts having a tapered shape that narrows in width from the base side to the tip side, the height of an intermediate part of the wall parts sandwiched between two adjacent hole parts being relatively low, and the height of the wall parts surrounded by three or more adjacent hole parts being relatively high. The method includes a film formation step of forming an anodic oxide film having a crown-shaped structure with a relatively high central portion; a film treatment step of irradiating plasma to the anodic oxide film formed by the film formation step to impart functional groups to the anodic oxide film to activate it; and a water-repellent step of providing a water-repellent material layer on the surface of the anodic oxide film by performing a water-repellent treatment on the anodic oxide film activated by the film treatment step using an aqueous solution containing a water-repellent material made of at least one compound selected from the group consisting of fluorine-containing compounds and silicon-containing compounds, and the ratio (H / W) of the hole depth (H) to the hole spacing (W) of the holes in the anodic oxide film is set to be 1 or more and 4 or less.
[0048] [2-1. Film formation process] First, in the film formation process, an anodized film is formed by repeatedly performing an anodizing treatment on an aluminum base material using an electrolyte containing oxalic acid and an etching treatment on the aluminum base material using a treatment solution containing phosphoric acid.
[0049] <Anodizing treatment> In the anodizing treatment, an oxide film is formed using oxalic acid as an electrolyte. This allows the substrate to have a relatively large pore size, which is suitable for achieving water repellency. The method of the anodizing treatment is not particularly limited and may be the same as a known method. For example, the surface of the aluminum substrate to be processed is anodized in an electrolyte under a constant voltage to form an oxide film.
[0050] Among these, the concentration of oxalic acid in the electrolytic solution is preferably 0.1% by mass or more, and more preferably 0.2% by mass or more, in order to stabilize the current value during anodization and, as a result, to reproducibly obtain the anodized film having the above-mentioned porous layer, while the concentration of oxalic acid is preferably 1% by mass or less, and more preferably 0.5% by mass or less.
[0051] Also, from the viewpoint of reproducibly obtaining the anodized film having the porous layer described above, the voltage during anodization is preferably 30V or more, preferably 60V or more. On the other hand, the voltage during anodization is preferably 100V or less, preferably 80V or less. Furthermore, the temperature of the electrolyte is preferably 30°C or less, preferably 15°C or less, and the temperature of the electrolyte is preferably 4°C or more, preferably 7°C or more. Furthermore, the time of anodization is preferably 60 seconds or more, preferably 80 seconds or more, and the time of anodization is preferably 180 seconds or less, preferably 120 seconds or less.
[0052] <Etching process> In addition, the etching process is performed using a treatment liquid containing phosphoric acid. By using a treatment liquid containing phosphoric acid, it is possible to selectively dissolve a portion of the alumina, which is the oxide film, without dissolving the aluminum of the aluminum base material. In other words, by repeatedly forming holes by a second subsequent anodization process while leaving a depression at the bottom of the porous layer, it is possible to enlarge (pore widen) the holes in the porous layer of the anodized film.
[0053] Here, the concentration of phosphoric acid in the treatment solution used in the etching process is preferably 0.5 mol / L or more, preferably 0.8 mol / L or more, and on the other hand, 3 mol / L or less, preferably 2 mol / L or less, from the viewpoint of being able to perform the selective dissolution of alumina as described above with good reproducibility. The temperature of the treatment solution in the etching process is preferably 10°C or more, preferably 20°C or more, and on the other hand, 50°C or less, preferably 40°C or less. Furthermore, the time required for the etching process is preferably 5 minutes or more, preferably 10 minutes or more, and on the other hand, 40 minutes or less, preferably 30 minutes or less. Usually, the etching process is performed multiple times, and the time required for the etching process here refers to the time required for one etching process.
[0054] In the present invention, the above-mentioned anodizing treatment and etching treatment must be repeated, and are performed at least in the order of anodizing treatment (first time), etching treatment (first time), and anodizing treatment (second time). To more reliably obtain an anodizing film having a desired porous layer, it is preferable to perform the anodizing treatment three or more times and the etching treatment two or more times, and more preferably, to perform the anodizing treatment five or more times and the etching treatment four or more times. In this way, by repeating the anodizing treatment and the etching treatment, an anodizing film having a wall portion with a crown-shaped structure is formed.
[0055] In the film formation process, the aluminum base material to be anodized and etched has a surface roughness (Ra) of preferably 0.1 μm or more, more preferably 0.2 μm or more, even more preferably 0.3 μm or more, and particularly preferably 0.5 μm or more. In general, when performing anodizing, cleaning and degreasing are performed, and then the surface is made uniform as a pretreatment by etching with an acid or alkaline solution, or by mirror finishing using electrolytic polishing or mechanical polishing. However, in the present invention, it is preferable to perform anodizing and etching in a state having the above-mentioned surface roughness without performing such surface uniformization treatment, and only by cleaning dirt, etc. The detailed reason has not been fully elucidated, but by using an aluminum base material having such surface roughness, the holes of the porous layer tend to be irregularly arranged with a large standard deviation of the hole angle θp as described above, and the domain structure D tends to be easily formed in the anodized film. As a result, it is considered that the durability of the water repellency is guaranteed. The surface roughness (Ra) represents the arithmetic mean roughness defined in JIS B 0601:2013.
[0056] [2-2. Coating process] Next, in the film treatment process, the anodic oxide film formed in the previous film formation process is irradiated with plasma to perform a plasma treatment to impart functional groups to the anodic oxide film, thereby activating it. In the present invention, an anodic oxide film having a porous layer with bottomed holes opening on the surface and walls standing around the holes, and having a crown-shaped wall structure is formed by repeating an anodizing process using oxalic acid and an etching process using phosphoric acid, and then activation by plasma treatment is performed before providing a water-repellent material layer, thereby increasing the affinity between the anodic oxide film and the water-repellent material, and allowing the water-repellent property to be maintained for a long period of time. Although the details of this mechanism are not necessarily clear, it is believed that the hydroxyl group (OH group) of about one molecule on the surface imparted by the plasma treatment is related to the improvement of the affinity with the water-repellent material. In addition, it is believed that the anodic oxide film has a porous layer with holes and walls, and the walls have a crown-shaped structure, which provides resistance to shape collapse due to plasma treatment and allows the water-repellent property to be maintained.
[0057] In other words, in the present invention, as described above, by setting the ratio (H / W) of the depth (H) of the pores in the anodized film to the spacing (W) within a relatively low range, the shape of the porous layer is prevented from collapsing when subjected to plasma treatment, making it possible to maintain water repellency. Furthermore, by covering the anodized film with a water-repellent material layer after activation by plasma treatment, the affinity between the anodized film and the water-repellent material is increased, and water repellency is more reliably maintained.
[0058] Here, the plasma treatment is not particularly limited as long as it can generate plasma in which gas molecules are ionized into positive ions and electrons to treat the surface of the anodized film on the aluminum substrate, and may be a plasma treatment using a plasma generator in a vacuum or low pressure, or may be a plasma treatment using a plasma generator at atmospheric pressure. 2 , Ar, O 2The gas to be used is preferably one selected from the group consisting of oxygen, air, and water vapor, or a mixture of two or more selected from the group consisting of oxygen, air, and water vapor. Among these, from the viewpoint of forming hydroxyl groups in the anodized film by plasma treatment, O 2 The gas used may include at least one gas selected from the group consisting of oxygen, air, and water vapor, and preferably, the anodized film is exposed to oxygen plasma to impart hydroxyl groups to the anodized film.
[0059] The plasma treatment conditions are not particularly limited, but the treatment pressure is 1.0×10 -1 Pa or more, preferably 3.0×10 -1 Pa or more, while 1.0×10 2 Pa or less, and preferably 7.0×10 1 The pressure should be 10 Pa or less. The power source should have an RF (ICP) power output of 100 W or more, preferably 300 W or more, more preferably 500 W or more, while it should be 2000 W or less, preferably 1500 W or less, more preferably 1000 W or less. The treatment time should be 3 minutes or more, preferably 8 minutes or more, while it should be 30 minutes or less, preferably 15 minutes or less.
[0060] [2-3. Water repellent process] In the water-repellent process, the anodized film activated by the film treatment process is subjected to a water-repellent treatment using an aqueous solution containing a water-repellent material made of at least one compound selected from the group consisting of fluorine-containing compounds and silicon-containing compounds, thereby forming a water-repellent material layer on the surface of the anodized film.
[0061] The aqueous solution used in the water-repellent treatment contains a water-repellent material made of either or both of the above-mentioned fluorine-containing compounds and silicon-containing compounds. The specific means of the water-repellent treatment are not particularly limited as long as they can form a water-repellent material layer on the surface of the anodized film, and known methods such as spraying, coating, and immersion can be used. After the water-repellent treatment, the water-repellent material layer may be formed on the surface of the anodized film by natural drying, or may be heated and dried at, for example, about 100°C to 300°C, or a combination of these may be used.
[0062] [2-4. Pretreatment process] A pretreatment step may be provided in which a pretreatment is performed on the surface of the aluminum substrate prior to the anodizing treatment in the film forming step. Examples of the pretreatment include washing and degreasing of the aluminum substrate. Washing can be performed using, for example, a surfactant, an acid, an alkali, etc. Degreasing can be performed using, for example, an organic solvent such as acetone, alcohol, or ethanol, an alkali, etc. When washing or degreasing is performed, rinsing with pure water may be performed as necessary.
[0063] [3. Effects] The water-repellent member of the present invention has an anodized film having a porous layer with bottomed holes opening on the surface and walls standing around the holes, and the walls have a crown-shaped structure, so that the water contact angle is 150° or more and water does not drip, as shown in the examples described below, and the water-repellent member exhibits super water-repellency. In addition, in the manufacturing method of the water-repellent member of the present invention, the anodized film is activated by plasma treatment and then covered with a water-repellent material layer, so that the affinity between the anodized film and the water-repellent material is increased and the water-repellent property is maintained. Furthermore, the water-repellent member of the present invention can maintain the water-repellent property by suppressing the shape of the porous layer from collapsing when subjected to plasma treatment, since the ratio (H / W) of the depth (H) to the spacing (W) of the holes in the anodized film is in a relatively low numerical range. That is, in the present invention, the anodized coating has a porous layer having holes and walls, and the walls have a crown-shaped structure, thereby achieving both water repellency and resistance to deformation caused by plasma treatment, thereby enabling the water repellency to be sustained.
[0064] In particular, in the present invention, a water-repellent member can be obtained by using an aluminum base material. Combined with the processability of aluminum, this can be said to have excellent industrial potential, as it can be deployed in a variety of applications and members, for example, to prevent adhesion of condensed water or dew formation that occurs in low-temperature and high-humidity environments, and to prevent snow, frost, or ice formation.
[0065] [4.Other] In the above-described embodiment, a method for calculating the length, angle, etc. of each element according to the present invention by printing an image of an SEM photograph and measuring the length has been described. Printing and measuring are not necessarily required for measurement. For example, calculations may be performed based on the relationship between each element included in the image of the SEM photograph displayed on a display and the length of the scale. Furthermore, the length, angle, etc. of each element may be measured by performing image analysis on the image of the SEM photograph. EXAMPLES
[0066] Hereinafter, preferred embodiments of the present invention will be described in detail based on examples and comparative examples, but the present invention is not limited thereto. Tables 1 to 3 show the manufacturing conditions in each example and comparative example, and various evaluations of the obtained water-repellent members.
[0067] [1. Shape evaluation] <Measurement of surface roughness (Ra) of aluminum substrate> The surface roughness (Ra) of the aluminum substrate was measured using a device named SURFTEST SJ-210 manufactured by Mitutoyo Corporation. The aluminum substrates of the examples and comparative examples were measured under the conditions of JIS B 0601-2013.
[0068] <Plane SEM observation> Planar observation was performed using an ultra-high resolution scanning electron microscope: ULTRA plus manufactured by Carl Zeiss Co., Ltd. For the water-repellent members of the examples and comparative examples, samples were sputtered with Pt for 30 to 60 seconds and observed at an acceleration voltage of 3 to 10 kV. For inclined surfaces, the sample stage was tilted at 45° and observed.
[0069] <Cross-section SEM observation> Cross-section observation was performed on the water-repellent members of the examples and comparative examples using a CROSS SECTION POLISHER IB-09020CP manufactured by JEOL Ltd. + The coating was processed with an ion beam to expose the cross section, and a sample was obtained by sputtering with Pt for 30 to 60 seconds, and the cross section was observed in the same manner as the planar observation.
[0070] <Measurement of hole spacing (Wp)> The method described above with reference to Fig. 5 was followed. For the following Examples 1 to 3 and Comparative Examples 1 and 5 to 7, three transverse lines L1 to L3 were arbitrarily drawn across the image of a planar SEM photograph at a magnification of 50,000 times, and the average value of the spacing between the holes adjacent to the three transverse lines L1 to L3 was calculated to obtain the spacing between the holes (Wp).
[0071] <Measurement of hole depth (Hp)> The method described above with reference to Fig. 6 was followed. For the following Examples 1 to 3 and Comparative Example 1, images of cross-sectional SEM photographs at a magnification of 50,000 times were used, and for Comparative Examples 5 to 7, images of cross-sectional SEM photographs at a magnification of 10,000 times were used, and straight lines L21 to L30 connecting the tip portions (tops) of adjacent wall portions were drawn, and straight lines L31 to L40 connecting the midpoints of these straight lines to the tip portions (bottoms) of the holes were drawn to determine the depths of the holes at 10 points, and the average value of the depths of the holes at 10 points was calculated to obtain the depth of the holes (Hp).
[0072] <Measurement of thickness (T) of anodic oxide film> The method described above with reference to Fig. 10 was followed. For the following Examples 1 to 3 and Comparative Example 1, cross-sectional SEM backscattered electron images at a magnification of 50,000 were used, and for Comparative Examples 2 to 7, cross-sectional SEM backscattered electron images at a magnification of 10,000 were used, a straight line corresponding to the film thickness was drawn to measure the film thickness at three points, and the film thicknesses at the three points were averaged to obtain the thickness (T) of the anodic oxide film.
[0073] <Measurement of the hole opening diameter (D)> The method described above with reference to Fig. 5 was followed. For the following Examples 1 to 3 and Comparative Examples 1 and 5 to 7, three transverse lines L1 to L3 were arbitrarily drawn across the image of a planar SEM photograph at a magnification of 50,000 times, and for each hole where the diameter of the opening was confirmed by passing through or contacting the lines, the maximum diameter of the opening at the position where the diameter was largest (maximum hole diameter) was measured, and the maximum hole diameters of all the holes were calculated by moving the transverse lines L1 to L3 up and down, respectively, and the average value of all the maximum hole diameters was taken as the hole diameter D of the opening.
[0074] <Measurement of wall base width (Ww)> The method described above with reference to Fig. 9 was followed. Cross-sectional SEM photographs at a magnification of 50,000 were used for the following Examples 1 to 3 and Comparative Example 1, and cross-sectional SEM photographs at a magnification of 10,000 were used for Comparative Examples 2 to 7, and straight lines L41 to L45 were drawn to calculate the base width of the wall at five points, and the base widths of the wall at five points were averaged to obtain the base width of the wall (Ww).
[0075] <Measurement of wall height (Hw)> The method described above with reference to Fig. 9 was followed. Cross-sectional SEM photographs at a magnification of 50,000 were used for the following Examples 1 to 3 and Comparative Example 1, and cross-sectional SEM photographs at a magnification of 10,000 were used for Comparative Examples 2 to 7, and straight lines L51 to L55 were drawn to calculate the heights of the wall at five points, and the heights of the wall at the five points were averaged to obtain the average wall height (Hw).
[0076] <Measurement of hole angle (θp)> The method described above with reference to FIG. 7 was followed. In the following Examples 1 to 3 and Comparative Example 1, a cross-sectional SEM photograph at a magnification of 50,000 times was used to draw straight lines L21 to L30, L31 to L40, L61 to 70, L71 to 80, and L81 to L90 at 10 locations where holes could be confirmed, and the angles of the 10 holes were calculated. The average value of the angles of the 10 holes was calculated to obtain the angle (θp) of the holes. In addition, the standard deviation was calculated as the variation in the angle of the holes for the angle θp of the holes thus obtained.
[0077] [2. Water repellency evaluation] Examples 1 to 3, Comparative Examples 1 to 8 The contact angle of water was measured using an automatic contact angle meter DMo-602 manufactured by Kyowa Interface Science Co., Ltd. The contact angle at this time was taken as the initial contact angle. In addition, to evaluate the durability of water repellency, the sample was placed in a salt spray device (SST: 5% NaCl, 35°C, compliant with the salt spray test method of JIS Z2371:2015) and the contact angle of water was measured after 500 hours and 1000 hours. Note that with this measuring device, water droplets do not land on the sample when the contact angle is 150° or more, which is super water repellent.
[0078] [3. Condensation evaluation] The water-repellent member of Example 1 and the hydrophilic member of Comparative Example 8, both in the form of a plate, were attached to the stainless steel inner wall of an explosion-proof refrigerator for chemicals (RP-400 manufactured by Nippon Freezer Co., Ltd.). After 1000 hours at a temperature setting of 5°C, the condensation state of each member and the inner wall of the refrigerator was visually observed. Members that did not condense were rated as excellent (◎), members that showed slight condensation were rated as fair (△), and members that condensed and dripped water droplets were rated as poor (×).
[0079] [4. Sample Preparation] [Example 1] <(1) Pretreatment> A5052P aluminum material with a length of 297 mm, width of 210 mm, thickness of 0.6 mm, and Ra: 0.19 μm was washed with a neutral detergent and ultrapure water. Specifically, the aluminum material was immersed in a cleaning solution prepared by diluting a neutral detergent, Semiclean M-1 (manufactured by Yokohama Yushi Kogyo Co., Ltd., product number (model number): 1251-3) (polyoxyethylene alkyl ether: 26%, ethanol: 1 to 5%, water: remaining amount) with water to 1% (volume ratio) at a temperature of 30°C for 5 minutes. Next, the aluminum material was rinsed with ultrapure water at a temperature of 25°C to 30°C for 10 minutes. Two sets of immersion in the cleaning solution and rinsing with ultrapure water were performed as one set, and this was used as pretreatment cleaning.
[0080] <(2) Anodizing> The pretreated aluminum material was anodized in a 0.3 mass% oxalic acid solution at a voltage of 80 V for 100 seconds at a temperature of 8±1°C.
[0081] <(3) Pore widening (etching process)> The anodized film was subjected to pore widening in a 1 mol / L phosphoric acid solution at 30°C for 20 minutes.
[0082] <(4) Enlargement of pores> The above-mentioned anodizing treatment was repeated five times and the pore widening treatment was repeated four times alternately to form an anodized film.
[0083] <(5) Plasma treatment> The anodized film that had been anodized and pore-widened was then sputtered in a vacuum deposition chamber at a pressure of 5.0×10 using a batch-type magnetron sputtering device manufactured by Geomatec Co., Ltd. -1 Pa (5.0E-1Pa) (Ar: 1500sccm, O 2 The anodic oxide film was activated by plasma treatment under the conditions of a plasma pressure of 400 sccm, RF (ICP) power output of 500 W for 10 minutes. In Table 2, the plasma treatment under these conditions is indicated as "medium" plasma conditions.
[0084] <(6) Water-repellent treatment> A solution was prepared by diluting UD-509 (active ingredient: 20%), a fluorine-containing silane coupling agent manufactured by Daikin Industries, Ltd., to 0.1% with Galden (registered trademark) HT-135, a perfluoropolyether fluorine-based fluid manufactured by Solvay Japan Co., Ltd. The aluminum material after the plasma treatment was immersed in this solution for 10 minutes, naturally dried, and then baked in air at 150°C for 1 hour. The excess was then removed, and a water-repellent material layer was formed to obtain the water-repellent member of Example 1.
[0085] The anodized coating of the water-repellent member according to Example 1 obtained above had a tapered shape in which the wall width narrowed from the base side to the tip side, as shown in Fig. 1 above. In addition, the wall portion of the porous layer had a crown-shaped structure in which the height of the intermediate portion sandwiched between two adjacent holes was relatively low, and the height of the central portion of the wall portion surrounded by three or more adjacent holes was relatively high, as shown in Fig. 2 (Example 1 crown shape + in plasma: inclination x 50000). In addition, the tip of the central portion C of the wall portion surrounded by three or more adjacent holes had a protruding portion C1 that protruded and spread like a whisker in the width direction of the wall portion.
[0086] The cross-sectional SEM images used to determine the pore spacing (W), pore depth (H), pore angle (θp), and wall base width (Ww) in this porous layer are shown in Figures 5, 6, 7, and 9.
[0087] Of these, from FIG. 5 (Example 1 crown shape + in plasma: surface x 50000), the average number of holes calculated from the three cross lines was 14.67, the average spacing between the holes was 162 nm, and the average maximum hole diameter of all the holes was 149 nm. Similarly, from FIG. 6, the average depth of the holes at 10 points was 498 nm. Furthermore, from FIG. 7, the average angle of the holes at 10 points was 91.7°, with a standard deviation of 4.77. Furthermore, from FIG. 9, the average base width of the wall at five points was 156 nm, and the average height of the wall at five points was 526 nm. FIG. 10 shows the cross-sectional SEM image used to determine the thickness of the anodic oxide film, and the average thickness of the anodic oxide film at three locations was 648 nm. The results obtained are summarized in Table 3. Furthermore, Fig. 11 (Example 1, crown shape + in plasma: flat surface x 10000) is a planar SEM image showing the domain structure that can be confirmed in the porous layer of the anodic oxide film.
[0088] [Example 2] The same pretreatment as in Example 1, as well as anodizing and pore widening were performed to enlarge the pores, to produce an anodized film. Plasma treatment was then performed in a vacuum deposition apparatus using a batch-type magnetron sputtering device manufactured by Geomatec Co., Ltd. at a pressure of 5.0 × 10 -1 Pa (5.0E-1Pa) (Ar: 1500sccm, O 2 The plasma treatment was carried out under the conditions of: (1) 0.015 ml / min, (2) 0.015 ml / min, (3) 0.015 ml / min, (4) 0.015 ml / min, (5) 0.015 ml / min, (6) 0.015 ml / min, (7) 0.015 ml / min, (8) 0.015 ml / min, (9) 0.015 ml / min
[0089] The anodized coating of the water-repellent member according to Example 2 obtained above had a tapered shape in which the wall width narrowed from the base side to the tip side, as shown in Fig. 12. In addition, the wall portion of the porous layer had a crown-shaped structure in which the height of the intermediate portion sandwiched between two adjacent holes was relatively low, and the height of the central portion of the wall portion surrounded by three or more adjacent holes was relatively high, as shown in Fig. 13(a) [Example 2 Crown shape + Plasma strength: Incline x 50000]. Furthermore, the tip of the central portion C of the wall portion surrounded by three or more adjacent holes had a protruding portion C1 that protruded and spread like a whisker in the width direction of the wall portion.
[0090] The planar SEM image used to determine the spacing (W) of the holes in the porous layer is shown in Figure 16(a) (Example 2, crown shape + strong plasma: surface x 50000). Similarly, the cross-sectional SEM image used to determine the depth (H) of the holes in the porous layer is as shown in Figure 12 above, and the cross-sectional SEM image used to determine the angle (θp) of the holes in the porous layer is shown in Figure 18. Similarly, the cross-sectional SEM image used to determine the base width (Ww) of the wall in the porous layer is shown in Figure 19(a) (Example 2, crown shape + strong plasma: cross-section x 50000), and further, the cross-sectional SEM image used to determine the thickness of the anodized film is shown in Figure 21(a) (Example 2, crown shape + strong plasma: cross-section x 50000).
[0091] From FIG. 16(a), the average number of holes calculated from the three cross-sectional lines was 14, the average spacing between the holes was 169 nm, and the average maximum diameter of all the holes was 163 nm. From FIG. 12, the average depth of the 10 holes was 583 nm. From FIG. 18, the average angle of the 10 holes was 90.3°, with a standard deviation of 5.16. From FIG. 19(a), the average base width of the wall at five points was 160 nm, and the average height of the wall at five points was 683 nm. From FIG. 21(a), the average thickness of the anodized film at three points was 763 nm. The results are shown in Table 3. Furthermore, as shown in Fig. 24(a) (Example 2, crown shape + strong plasma: gradient x 10000), it was confirmed that the porous layer in the anodized coating of the water-repellent member according to Example 2 also had a domain structure.
[0092] [Example 3] The same pretreatment as in Example 1, as well as anodizing and pore widening were performed to produce an anodized film. Plasma treatment was performed using a batch-type magnetron sputtering device manufactured by Geomatec Co., Ltd. at a pressure of 5.0 × 10 -1 Pa (5.0E-1Pa) (Ar: 1500sccm, O 2The plasma treatment was carried out under the conditions of: (a) 1000W (400sccm) and RF (ICP) power output of 1000W for 10 minutes. The plasma treatment under these conditions is referred to as "strong" in Table 2. Thereafter, the same water repellent treatment as in Example 1 was carried out.
[0093] The anodized film of the water-repellent member according to Example 3 obtained above had a tapered shape in which the width of the wall portion narrowed from the base side toward the tip side, as shown in FIG. 27. In addition, as shown in FIG. 13(b) [Example 3 Crown shape + strong plasma: inclination x 50000], the wall portion of the porous layer had a crown-shaped structure in which the height of the intermediate portion sandwiched between two adjacent holes was relatively low, and the height of the central portion of the wall portion surrounded by three or more adjacent holes was relatively high. In addition, the tip of the central portion C of the wall portion surrounded by three or more adjacent holes had a protruding portion C1 that protruded and spread like a whisker in the width direction of the wall portion. However, the water-repellent member according to Example 3 had relatively few crown-shaped structures compared to the cases of Examples 1 and 2.
[0094] The planar SEM image used to determine the spacing (W) of the holes in the porous layer is shown in Figure 16(b) (Example 3, crown shape + strong plasma: surface x 50000). Similarly, the cross-sectional SEM image used to determine the depth (H) of the holes in the porous layer is as shown in Figure 27, and the cross-sectional SEM image used to determine the angle (θp) of the holes in the porous layer is shown in Figure 28. Similarly, the cross-sectional SEM image used to determine the base width (Ww) of the wall in the porous layer is shown in Figure 19(b) (Example 3, crown shape + strong plasma: cross section x 50000), and further, the cross-sectional SEM image used to determine the thickness of the anodized film is shown in Figure 21(b) (Example 3, crown shape + strong plasma: cross section x 50000).
[0095] From FIG. 16(b), the average number of holes calculated from the three cross-sectional lines was 13.3, the average spacing between the holes was 174 nm, and the average maximum diameter of all the holes was 160 nm. From FIG. 27, the average depth of the ten holes was 276 nm. From FIG. 28, the average angle of the ten holes was 89.7°, with a standard deviation of 9.39. From FIG. 19(b), the average base width of the wall at five points was 184 nm, and the average height of the wall at five points was 334 nm. From FIG. 21(b), the average thickness of the anodized film at three points was 532 nm. The results obtained are shown in Table 3. Furthermore, as shown in Fig. 24(b) (Example 3, crown shape + strong plasma: tilt x 10000), it was confirmed that the porous layer in the anodized coating of the water-repellent member according to Example 3 also had a domain structure.
[0096] [Comparative Example 1] The same pretreatment as in Example 1, as well as anodization and pore widening were performed to enlarge the pores, but no plasma treatment was performed. The same water-repellent treatment as in Example 1 was performed to obtain a water-repellent member according to Comparative Example 1.
[0097] The anodized coating of the water-repellent member according to Comparative Example 1 obtained above had a tapered shape in which the wall width narrowed from the base side to the tip side, as shown in Fig. 29. In addition, the wall portion of the porous layer had a crown-shaped structure in which the height of the intermediate portion sandwiched between two adjacent holes was relatively low, and the height of the central portion of the wall portion surrounded by three or more adjacent holes was relatively high, as shown in Fig. 13(c) [Comparative Example 1 Crown Shape + No Plasma: Slope x 50000]. In addition, the tip of the central portion C of the wall portion surrounded by three or more adjacent holes had a protruding portion C1 that protruded and spread like a whisker in the width direction of the wall portion.
[0098] The planar SEM image used to determine the spacing (W) of the holes in the porous layer is shown in Fig. 16(c) (Comparative Example 1, crown shape x 50,000). Similarly, the cross-sectional SEM image used to determine the depth (H) of the holes in the porous layer is as shown in Fig. 29, and the cross-sectional SEM image used to determine the angle (θp) of the holes in the porous layer is shown in Fig. 30. Similarly, the cross-sectional SEM image used to determine the base width (Ww) of the wall in the porous layer is shown in Fig. 19(c) (Comparative Example 1, crown shape: cross-section x 50,000), and further, the cross-sectional SEM image used to determine the thickness of the anodized film is shown in Fig. 21(c) (Comparative Example 1, crown shape + no plasma: cross-section x 50,000).
[0099] From FIG. 16(c), the average number of holes calculated from the three cross-sectional lines was 14.3, the average spacing between holes was 164 nm, and the average maximum diameter of all holes was 158 nm. From FIG. 29, the average depth of the ten holes was 572 nm. From FIG. 30, the average angle of the ten holes was 89.4°, with a standard deviation of 3.83. From FIG. 19(c), the average base width of the wall at five points was 160 nm, and the average height of the wall at five points was 662 nm. From FIG. 21(c), the average thickness of the anodized film at three points was 692 nm. The results are shown in Table 3. Furthermore, as shown in Fig. 24(c) (Comparative Example 1, crown shape + no plasma: tilt x 10000), it was confirmed that the porous layer in the anodized coating of the water-repellent member according to Comparative Example 1 also had a domain structure.
[0100] [Comparative Example 2] The same pretreatment, anodizing treatment, and pore widening as in Example 1 were performed, but the anodizing treatment and pore widening were each performed only once to produce an anodized film. Next, the same water repellent treatment as in Example 1 was performed without performing plasma treatment.
[0101] As shown in Fig. 21(d) [Comparative Example 2, anodization once: cross section x 10000], an anodized film of a predetermined thickness was formed on the water-repellent member according to Comparative Example 2 obtained above. However, as shown in Fig. 13(d) [Comparative Example 2, anodization once: inclined x 50000], a crown-shaped structure could not be confirmed in the porous layer, but a mesh-like structure was observed. Incidentally, as shown in Fig. 21(d), the average thickness of the anodized film at three locations was 962 nm. In addition, as shown in Fig. 24(d) [Comparative Example 2, anodization once: x 10000], no domain structure was confirmed in the porous layer from the planar SEM image of the anodized film.
[0102] [Comparative Example 3] An anodized film was produced by carrying out the same pretreatment, anodizing treatment, and pore widening as in Comparative Example 2. Next, plasma treatment was carried out under the same "medium" conditions as in Example 1, and then water repellent treatment was carried out as in Example 1.
[0103] As shown in Fig. 22(a) [Comparative Example 3, anodization once + in plasma: cross section x 10000], an anodized film of a predetermined thickness was formed on the water-repellent member according to Comparative Example 3 obtained above. However, as shown in Fig. 14(a) [Comparative Example 3, anodization once + in plasma: inclined x 50000], a crown-shaped structure could not be confirmed in the porous layer, but a mesh-like structure was observed. Incidentally, as shown in Fig. 22(a), the average thickness of the anodized film at three locations was 811 nm. In addition, as shown in Fig. 25(a) [Comparative Example 3, anodization once + in plasma: x 10000], no domain structure was confirmed in the porous layer from the planar SEM image of the anodized film.
[0104] [Comparative Example 4] An anodized film was produced by carrying out the same pretreatment, anodizing treatment, and pore widening as in Comparative Example 2. Next, plasma treatment was carried out under the same strong conditions as in Example 2, and then water repellent treatment was carried out as in Example 1.
[0105] As shown in FIG. 22(b) [Comparative Example 4, anodization once + strong plasma: cross section x 10000], an anodized film of a predetermined thickness was formed on the water-repellent member according to Comparative Example 4 obtained above. However, as shown in FIG. 14(b) [Comparative Example 4, anodization once + strong plasma: inclined x 50000], a crown-shaped structure could not be confirmed in the porous layer, but a mesh-like structure was observed. Incidentally, as shown in FIG. 22(b), the average thickness of the anodized film at three locations was 1257 nm. In addition, as shown in FIG. 25(b) [Comparative Example 4, anodization once + strong plasma: x 10000], no domain structure was confirmed in the porous layer from the planar SEM image of the anodized film.
[0106] [Comparative Example 5] The same pretreatment as in Example 1, anodizing treatment, and pore widening were performed, but the anodizing treatment was performed under the conditions of a 0.3 mass% oxalic acid solution at a voltage of 120 V, a time of 120 seconds, and a temperature of 8±1° C., and the pore widening was performed with a 1 mol / L phosphoric acid solution at a temperature of 30° C. and a time of 20 minutes. Anodizing treatment was performed five times and pore widening treatment was performed four times alternately to produce an anodized film. No plasma treatment was performed, and then the same water repellent treatment as in Example 1 was performed.
[0107] The anodized coating of the water-repellent member according to Comparative Example 5 obtained above had a tapered shape in which the width of the wall portion narrowed from the base side to the tip side, as shown in FIG. 31. In addition, as shown in FIG. 14(c) [Comparative Example 5 Anodization + PW number: Incline × 50000], the wall portion of the porous layer had a crown-like structure in which the height of the intermediate portion sandwiched between two adjacent holes was relatively low, and the height of the center portion of the wall portion surrounded by three or more adjacent holes was relatively high. In addition, the tip of the center portion C of the wall portion surrounded by three or more adjacent holes had a protruding portion C1 that protruded and spread like a whisker in the width direction of the wall portion, but the porous layer of the anodized coating was relatively thick and columnar compared to the case of the Example.
[0108] The planar SEM image used to determine the spacing (W) of the pores in the porous layer is shown in Fig. 16(d) (Comparative Example 5, columnar shape: surface x 50,000). Similarly, the cross-sectional SEM image used to determine the depth (H) of the pores in the porous layer is as shown in Fig. 31. Similarly, the cross-sectional SEM image used to determine the base width (Ww) of the wall in the porous layer is shown in Fig. 19(d) (Comparative Example 5, columnar shape: cross-section x 10,000), and further, the cross-sectional SEM image used to determine the thickness of the anodized film is shown in Fig. 22(c) (Comparative Example 5, anodization + PW several times: cross-section x 10,000).
[0109] Of these, from FIG. 16(d), the average number of holes calculated from the three cross lines was 10, the average spacing between the holes was 235 nm, and the average maximum hole diameter of all the holes was 192 nm. Also, from FIG. 31, the average depth of the holes at 10 points was 4325 nm. Furthermore, from FIG. 19(d), the average base width of the wall at five points was 236 nm, and the average height of the wall at five points was 4150 nm. Furthermore, from FIG. 22(c), the average thickness of the anodized film at three points was 4375 nm. The results are shown in Table 3. Furthermore, as shown in Fig. 25(c) (Comparative Example 5, anodization + PW number: x 10000), it was confirmed that the porous layer in the anodized coating film of the water-repellent member according to Comparative Example 5 also had a domain structure.
[0110] [Comparative Example 6] An anodized film was produced by carrying out the same pretreatment as in Comparative Example 5, anodizing treatment, and enlarging the pores by pore widening. The plasma treatment was carried out under the same conditions as in Example 1, and then the same water repellent treatment as in Example 1 was carried out.
[0111] The anodized film of the water-repellent member according to Comparative Example 6 obtained above had a tapered shape in which the width of the wall portion narrowed from the base side to the tip side, as shown in Fig. 32. In addition, as shown in Fig. 14(d) [Comparative Example 6 Anodization + PW several times + in plasma: tilt × 50000], the wall portion of the porous layer had a crown-like structure in which the height of the intermediate portion sandwiched between two adjacent holes was relatively low, and the height of the center portion of the wall portion surrounded by three or more adjacent holes was relatively high. In addition, the tip of the center portion C of the wall portion surrounded by three or more adjacent holes had a protruding portion C1 that protruded and spread like a whisker in the width direction of the wall portion, but the porous layer of the anodized film was relatively thick and columnar compared to the case of the Example.
[0112] The planar SEM image used to determine the spacing (W) of the pores in the porous layer is shown in Figure 17(a) (Comparative Example 6, columnar shape + in plasma: surface x 50,000). Similarly, the cross-sectional SEM image used to determine the depth (H) of the pores in the porous layer is as shown in Figure 32. Similarly, the cross-sectional SEM image used to determine the base width (Ww) of the wall in the porous layer is shown in Figure 20(a) (Comparative Example 6, anodization + PW several times + in plasma: cross-section x 10,000), and further, the cross-sectional SEM image used to determine the thickness of the anodized film is shown in Figure 22(d) (Comparative Example 6, anodization + PW several times + in plasma: cross-section x 10,000).
[0113] From Fig. 17(a), the average number of holes calculated from the three cross-sectional lines was 11, the average spacing between the holes was 214 nm, and the average maximum hole diameter of all the holes was 174 nm. Also, from Fig. 32, the average depth of the holes at 10 points was 3197 nm. Furthermore, from Fig. 20(a), the average base width of the wall at five points was 218 nm, and the average height of the wall at five points was 3433 nm. Furthermore, from Fig. 22(d), the average thickness of the anodized film at three points was 3420 nm. The results are shown in Table 3. Furthermore, as shown in Fig. 25(d) (Comparative Example 6: anodization + PW several times + in plasma: x 10000), it was confirmed that the porous layer in the anodized coating of the water-repellent member according to Comparative Example 6 also had a domain structure.
[0114] [Comparative Example 7] An anodized film was produced by carrying out the same pretreatment as in Comparative Example 6, anodizing treatment, and enlarging the pores by pore widening. The plasma treatment was carried out under the same strong conditions as in Example 2, and then the same water repellent treatment as in Example 1 was carried out.
[0115] The anodized coating of the water-repellent member according to Comparative Example 7 obtained above had a tapered shape in which the width of the wall portion narrowed from the base side to the tip side, as shown in Fig. 33. In addition, as shown in Fig. 15 (Comparative Example 7 Anodization + PW several times + plasma strength: tilt × 50000), the wall portion of the porous layer had a crown-like structure in which the height of the intermediate portion sandwiched between two adjacent holes was relatively low, and the height of the center portion of the wall portion surrounded by three or more adjacent holes was relatively high. In addition, the tip of the center portion C of the wall portion surrounded by three or more adjacent holes had a protruding portion C1 that protruded and spread like a whisker in the width direction of the wall portion, but the porous layer of the anodized coating had a relatively thick columnar shape compared to the case of the Example.
[0116] The planar SEM image used to determine the spacing (W) of the pores in the porous layer is shown in Figure 17(b) (Comparative Example 7, columnar shape + strong plasma: surface x 50,000). Similarly, the cross-sectional SEM image used to determine the depth (H) of the pores in the porous layer is as shown in Figure 33. Similarly, the cross-sectional SEM image used to determine the base width (Ww) of the wall in the porous layer is shown in Figure 20(b) (Comparative Example 7, anodization + PW several times + strong plasma: cross-section x 10,000), and further, the cross-sectional SEM image used to determine the thickness of the anodized film is shown in Figure 23(a) (Comparative Example 7, anodization + PW several times + strong plasma: cross-section x 10,000).
[0117] From Fig. 17(b), the average number of holes calculated from the three cross-sectional lines was 11.7, the average spacing between the holes was 202 nm, and the average maximum diameter of all the holes was 184 nm. Also, from Fig. 33, the average depth of the holes at ten points was 3667 nm. Furthermore, from Fig. 20(b), the average base width of the wall at five points was 223 nm, and the average height of the wall at five points was 3494 nm. Furthermore, from Fig. 23(a), the average thickness of the anodized film at three points was 3835 nm. The results are shown in Table 3. Furthermore, as shown in Fig. 26 (Comparative Example 7, anodization + several PW cycles + strong plasma: x 10000), it was confirmed that the porous layer in the anodized coating of the water-repellent member according to Comparative Example 6 also had a domain structure.
[0118] [Comparative Example 8] An anodized film was formed in the same manner as in Example 1. Then, in the same manner as in Example 1, plasma treatment was performed in a vacuum deposition apparatus using a batch-type magnetron sputtering device manufactured by Geomatec Co., Ltd. at a pressure of 5.0×10 -1 Pa (5.0E-1Pa) (Ar: 1500sccm, O 2 The test was performed under the conditions of a heating rate of 400 sccm, and an RF (ICP) power output of 500 W for 10 minutes. Thereafter, a part was cut out without carrying out a water-repellent treatment, and a member of Comparative Example 8 (hydrophilic member) was obtained in which a hydrophilic coating was formed on the surface of the aluminum member.
[0119] As shown in FIG. 34, the anodized film of the water-repellent member according to Comparative Example 8 obtained above had a tapered shape in which the wall width narrowed from the base side to the tip side.
[0120] The planar SEM image used to determine the spacing (W) of the holes in the porous layer is shown in Fig. 17(c) (Comparative Example 8, crown shape + in plasma: surface x 50000). Similarly, the cross-sectional SEM image used to determine the depth (H) of the holes in the porous layer is as shown in Fig. 34, and the cross-sectional SEM image used to determine the angle (θp) of the holes in the porous layer is shown in Fig. 35. Similarly, the cross-sectional SEM image used to determine the base width (Ww) of the wall in the porous layer is shown in Fig. 20(c) (Comparative Example 8, crown shape + strong plasma: cross-section x 50000), and further, the cross-sectional SEM image used to determine the thickness of the anodized film is shown in Fig. 23(b) (Comparative Example 8, crown shape + in plasma: cross-section x 50000).
[0121] From FIG. 17(c), the average number of holes calculated from the three cross lines was 14.67, the average spacing between holes was 167 nm, and the average maximum diameter of all holes was 157 nm. From FIG. 34, the average depth of the ten holes was 524 nm. From FIG. 35, the average angle of the ten holes was 88.7°, with a standard deviation of 13.1. From FIG. 20(c), the average base width of the wall at five points was 159 nm, and the average height of the wall at five points was 532 nm. From FIG. 23(b), the average thickness of the anodized film at three points was 646 nm. The results obtained are summarized in Table 3.
[0122] [5. Evaluation Results] In Examples 1 to 3 and Comparative Example 1, the porous layer of the anodized film had a crown shape. In Examples 1 to 3, no droplets were deposited after 500 hours of salt spray testing (SST), and super-water repellency was maintained. On the other hand, in Comparative Example 1, which was crown-shaped and not subjected to plasma treatment, no droplets were deposited initially, but after SST, super-water repellency was not maintained as compared to Examples 1 to 3, which were plasma treated. As a result, it is considered that the super-water repellency is not maintained unless plasma treatment is performed, because the silane coupling agent is easily detached. It is considered that in Example 3, the protruding part at the tip of the crown in the porous layer of the anodized film was scraped off due to the plasma conditions, resulting in a result that is slightly inferior in durability compared to other Examples.
[0123] On the other hand, in Comparative Examples 2 to 4, the porous layer of the anodized film has a network structure with small irregularities, and does not have a crown-shaped structure. In Comparative Examples 2 to 4, the initial contact angle was low and the film was not super-water-repellent. In Comparative Example 2, which did not undergo plasma treatment, the film became super-hydrophilic after 1000 hours of SST, and there is a possibility that the silane coupling agent in the fluorine treatment was completely removed, as in Comparative Example 1.
[0124] In addition, in Comparative Examples 5 to 7, the porous layer of the anodized film had a thick uneven shape (thick columnar structure), so initially, droplets did not adhere and the super water repellency was exhibited, but after SST, the contact angle decreased and the super water repellency was not sustained. In Comparative Examples 5 to 7, the anodized film had a columnar structure, large unevenness, and a large contact area, so the water repellency would likely be sustained, but in Comparative Example 5, no plasma treatment was performed, and in Comparative Examples 6 and 7, the shape of the wall of the anodized film was partially collapsed, so it is considered that the water repellency was inferior to that of the crown shape in Examples 1 to 3. Furthermore, in Comparative Examples 6 and 7, the ratio (H / W) of the depth (H) to the spacing (W) of the pores exceeded 4, so the shape of the wall of the anodized film was easily collapsed when the film was subjected to anodizing treatment and pore widening, or plasma treatment, resulting in poor water repellency.
[0125] In Comparative Example 8, an anodized film was formed and subjected to plasma treatment in the same manner as in Example 1, but since no water-repellent treatment was performed, the initial water contact angle was 10°, which was superhydrophilic. Furthermore, regarding the evaluation of condensation, as shown in FIG. 36, condensation occurred and water droplets dripped on the inner wall of the refrigerator and the hydrophilic member of Comparative Example 8 that had not been subjected to the water-repellent treatment, but no condensation was observed at all on the water-repellent member of Example 1.
[0126] The manufacturing conditions and evaluation results of the water-repellent members of Examples 1 to 3 and Comparative Examples 1 to 8 are summarized in Tables 1 to 3.
[0127] [Table 1]
[0128] [Table 2]
[0129] [Table 3]
[0130] As described above, the water-repellent member of the present invention exhibits high water repellency and can maintain the water-repellent performance for a long period of time.
Claims
1. A water-repellent member comprising an aluminum member having an aluminum base material made of aluminum or an aluminum alloy and an anodized film formed on a surface of the aluminum base material, and a water-repellent material layer containing a water-repellent material and covering a surface of the anodized film of the aluminum member, the water-repellent material layer contains at least one compound selected from the group consisting of a fluorine-containing compound and a silicon-containing compound, the anodized coating has a porous layer having a bottomed hole portion that opens to a surface and a wall portion that stands around the hole portion, the wall portion has a tapered shape in which the width narrows from the base side toward the tip side, and has a crown-like structure in which the height of an intermediate portion of the wall portion sandwiched between two adjacent ones of the hole portions is relatively low, and the height of a central portion of the wall portion surrounded by three or more adjacent ones of the hole portions is relatively high, The ratio (Hp / Wp) of the depth (Hp) of the hole to the spacing (Wp) of the hole is 1 or more and 4 or less. A water-repellent member.
2. The wall portion has a tapered shape in which the width narrows from the base side toward the tip side, and has a protruding portion that protrudes and expands in the width direction at the tip end portion of the center of the wall portion. The water-repellent member according to claim 1 .
3. The anodized coating has a standard deviation of the hole angle (θp) of 3 or more. The water-repellent member according to claim 1 .
4. The anodic oxide coating has a width (Ww) of the base of the wall portion of 100 nm or more. The water-repellent member according to claim 1 .
5. The anodic oxide coating has a thickness of 1 μm or less. The water-repellent member according to claim 1 .
6. the anodized coating has a domain structure in which a recess is formed by a group of the holes sandwiching a wall portion having a height lower than that of the surrounding wall portions, The water-repellent member according to claim 1 .
7. The water-repellent member is a condensation prevention member. The water-repellent member according to any one of claims 1 to 6.
8. A method for producing a water-repellent member comprising: an aluminum member having an aluminum base material made of aluminum or an aluminum alloy and an anodized coating film formed on a surface of the aluminum base material; and a water-repellent material layer containing a water-repellent material and covering a surface of the anodized coating film of the aluminum member, the method comprising the steps of: a film formation process in which anodizing treatment is performed on the aluminum base material using an electrolyte containing oxalic acid, and an etching treatment is performed on the aluminum base material using a treatment liquid containing phosphoric acid, and thereby a porous anodic oxide film is formed by the anodizing treatment and pore widening by the etching treatment, and thereby the anodic oxide film is formed, which has a porous layer having bottomed holes opening on the surface and wall portions standing around the holes, and the wall portions have a tapered shape that narrows in width from the base side to the tip side, and the height of an intermediate portion of the wall portion sandwiched between two adjacent holes is relatively low, and the height of a central portion of the wall portion surrounded by three or more adjacent holes is relatively high, and the anodic oxide film has a crown-shaped structure; a film treatment step of irradiating the anodized film formed in the film formation step with plasma to impart functional groups to the anodized film, thereby activating the anodized film; and a water-repellent process for performing a water-repellent treatment on the anodized film activated by the film treatment process using an aqueous solution containing a water-repellent material made of at least one compound selected from the group consisting of fluorine-containing compounds and silicon-containing compounds, thereby forming a water-repellent material layer on the surface of the anodized film; The pores of the anodized coating have a ratio (H / W) of the depth (H) of the pores to the spacing (W) of the pores of the anodized coating of 1 or more and 4 or less. A method for producing a water-repellent member.
9. the plasma treatment is an oxygen plasma treatment in which hydroxyl groups are imparted to the anodized film by irradiation with oxygen plasma; A method for producing the water-repellent member according to claim 8.
10. In the film forming step, the surface roughness (Ra) of the aluminum base material to be subjected to the anodizing treatment and the etching treatment is 0.1 μm or more. A method for producing the water-repellent member according to claim 8.
Citation Information
Patent Citations
Smooth surface with high-pressure stability, light transmittance, and self-healing properties.
JP2014509959A
Water-repellent substrate and manufacturing method therefor
JP2017115219A
Metallic member
JP2021116451A
Method for producing an anodic oxide coating on an aluminum alloy with a superhydrophobic surface
JP2022524167A